Ising model on Cayley trees: a new class of Gibbs measures and their comparison with known ones. (18th September 2017) - Rahmatullaev, M M; Rozikov, U A
Abstract: For the Ising model on Cayley trees we give a very wide class of new Gibbs measures. We show that these new measures are extreme under some conditions on the temperature. We give a review of all known Gibbs measures of the Ising model on trees and compare them with our new measures.